(untitled) (Journal of Asian Development Studies, 2023)
This study tests the predictions of two approaches against Universal Grammar for L2 acquisition of uninterpretable functional features in adult interlanguage grammars: representational deficit hypothesis maintains that adult L2 learners can never acquire features absent in their L1, suggesting that fossilization is inevitable (Hawkins & Franceschina 2004, Franceschina 2005), while full transfer/full access hypothesis claims that L2 uninterpretable functional features are initially transferred from the L1 and remain acquirable in adults (White et al. 2004, Leung 2005). To test these hypotheses, this study examines whether adult native speakers of less gender-sensitive languages such as Pashto/Balochi can acquire gender concord in an L2 like Urdu. The study investigates the Pashto and Balochi speakers’ online sensitivity to gender agreement violations in their L2 Urdu. A total of 90 participants participated in this study, including 30 L2 speakers of Balochi, 30 L2 speakers of Pashto, and 30 native Urdu speakers who served as the control group. The speeded grammaticality judgment task was used for this study. The findings reveal participants were sensitive to morphosyntactic gender agreement violations in L2 Urdu. While L1 background did not significantly affect overall responses in the participant analysis, the item analysis showed significant group differences and interaction effects, indicating L1 influence on judgments for specific items.